PENGALAMAN PENDERITA LUKA DIABETES DENGAN POLA PERAWATAN HOME VISIT DI KLINIK IIN WOUND CARE CIBITUNG, BEKASI - Indah Puspitasari; Oktavia Budianti; Asih Minarningtyas (Jurnal Ilmiah Keperawatan IMELDA, 2022)
Background : Diabetes Mellitus that is not controlled and handled can be a serious problem. The increase in the number of patients with diabetes mellitus will exacerbate the increased risk of developing diabetic wounds. One of the efforts of diabetic wound patients to optimize their recovery is by using health care services at home visits. Objective: The research was to explore in depth the experiences of diabetic wound patients who received Home Visit care patterns. Methods: This research design uses a qualitative method with a phenomenological study. Data collection was carried out by in-depth interviews on 6 diabetic wound patients who underwent wound care at home visits. Patients were selected by purposive sampling. Results: the study found five themes, namely the reasons for choosing to do treatment at a home visit, experiences while receiving care at a home visit, obstacles experienced during a home visit, efforts to overcome obstacles, and expectations for future home visit care. Suggestion: For further researchers, it is hoped that it can be used as basic data for further research and can take advantage of the categories generated in this research.